Cultivo hidropônico de agrião (nasturtium officinale) com diferentes concentrações de sulfato de magnésio - Barbieri, Leonardo (2022)
The watercress (Nasturtium officinale) is a herbaceous plant that belongs to the Family of Brassicaceae, a plant well adapted to moist soils due to its aquatic roots, a characteristic that provided a good development of the plant in hydroponic system. Magnesium is an important nutrient for chlorophyll production, phosphorus absorption, among other important components for the development of nutritional and visual quality of the plant. The objective of this work was to evaluate the production of watercress under different concentrations of magnesium sulfate in hydroponic system, aiming to improve the visual quality of plants. The experiment was carried out in the experimental area of Olericulture of the Federal Technological University of Paraná (UTFPR), Campus Dois Vizinhos. The experiment was conducted in a protected environment in the nutrient laminar flow system (NFT), using a completely randomized design (IHD), in a 2 x 5 factorial scheme with five replications, where factor 1: two species of watercress, land watercress (Barbarea verna) and watercress (Rorippa nasturtium-aquaticum L.) cv. Giant Broad Leaf, factor 2: magnesium sulfate concentrations, where the levels were: Standard dose (0.4g L-1), (0.42g L-1), (0.44 g L- 1), (0.46 g L-1) and (0.48 g L-1) magnesium sulfate (MgSO4), of the solution proposed by Furlani. The variables analyzed were: relative chlorophyll index, fresh and dry matter of shoots and roots, soluble pH, soluble solids (°BRIX), moisture and nutrients of plant tissue (N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn). The results obtained show that the increase in mgso4 doses contribute to the increase of chlorophyll content and fresh and dry mass, being the best result observed at the dose of (0.48 g L-1). The macronutrient content mostly did not show significant differences with the increase in doses. The increase in magnesium doses in the nutrient solution contributes to a better development of the crop, thus improving the productivity and visual quality of the plant.